2017
DOI: 10.4103/ejd.ejd_4_17
|View full text |Cite
|
Sign up to set email alerts
|

On the synthesis and characterization of β-tricalcium phosphate scaffolds coated with collagen or poly (D, L-lactic acid) for alveolar bone augmentation

Abstract: Objectives:After tooth loss, dimensional alterations on the alveolar bone ridge can occur that can negatively affect the placement of dental implants. The purpose of this study was to evaluate the synthesis, and mechanical properties of β-tricalcium phosphate (β-TCP) scaffolds coated with bioabsorbable polymers, namely, collagen and poly (D, L-lactic acid) (PDLLA).Materials and Methods:β-TCP powder was obtained by reactive milling and then characterized by X-ray diffraction and scanning electron microscopy/ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…The three-dimensional scaffold structure becomes an extracellular matrix that is similar or analogous as a template and physical support to guide cell proliferation and differentiation. 23 The three-dimensional scaffold must have high porosity and porous interconnected structures that will be able to facilitate cell attachment, proliferation, and differentiation. 24 25 Based on the SEM analysis as shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The three-dimensional scaffold structure becomes an extracellular matrix that is similar or analogous as a template and physical support to guide cell proliferation and differentiation. 23 The three-dimensional scaffold must have high porosity and porous interconnected structures that will be able to facilitate cell attachment, proliferation, and differentiation. 24 25 Based on the SEM analysis as shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that the shape and size of scaffold pores of bioscaffold materials could affect the migration and growth of seed cells, and ideal pore size should be controlled between 100 and 400 μm ( Deschamps et al, 2017 ). In this study, the pores of HG-HA-TCP scaffold were uniformly distributed; its internal morphology was analogous to that of natural cancellous bone with good integrity of pore wall.…”
Section: Discussionmentioning
confidence: 99%
“…From a mechanical viewpoint, the scaffold should have a strength equal to or even greater than the bone to be repaired [ 30 ]. The mechanical properties of the scaffold should match the original bone that can support various external loads, at least during the tissue regeneration process that is ongoing until osseointegration [ 31 , 32 , 33 ]. The highest average pressure of the 3DPP scaffold (273 ± 20.8 Kgf) will produce a compressive strength of about 24 MPa which resembles human cancellous bone (11–24 MPa), higher than trabecular bone (2–12 MPa) yet much lower than cortical bone (100–250 MPa) [ 30 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%